Chemical constituents, biological functions and pharmacological effects for comprehensive utilization of Eucommia ulmoides Oliver - Yi-Fan Xing; Dong He; Yi Wang; Wen Zeng; Chong Zhang; Yuan Lu; Nan Su; Yan-Hua Kong; Xin-Hui Xing (Food Science and Human Wellness)
Eucommia ulmoides Oliver is a native plant and valuable tonic Chinese medicine in China with a long history, great economic value and comprehensive development potential. Traditionally, the comprehensive utilization rate of E. ulmoides Oliv. is still very low, only bark has been used as medicine and other parts of Eucommia ulmoides Oliv. cannot be fully utilized, even the leaves have been well utilized in food products in Japan in the past decades. In order to improve the comprehensive utilization efficiency of E. ulmoides Oliv., in this review, we summarized the varieties and contents of main active compounds, biological functions and pharmacological effects in different parts of E. ulmoides Oliv. The findings suggest that other parts of E. ulmoides Oliv. could replace the bark of E. ulmoides Oliv. to some extent besides of their respective applications. The unique and extensive physiological functions between different parts of E. ulmoides Oliv. indicate that the comprehensive utilization of E. ulmoides Oliv. has a wide space to develop, which is also an effective way to protect E. ulmoides Oliv. resources and improve its the utilization rate. Keywords: Eucommia ulmoides Oliver, Comprehensive utilization, Chemical constituents, Biological functions, Pharmacological effects